طبيق تعليم كتاب "نحو أبستراك" لترقية مهارة قراءة الكتاب التراثي في المدرسة الدينية بمعهد إرشاد العباد كنوكواتو غورو جومبانج - Ali Maskur, Muhammad; Qomariyah, Lailatul (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
This study aims to explore and analyze the application of the Nahwu Abstrak teaching method to improve the ability to read classical Islamic texts (kitab kuning) at Madrasah Diniyah Pondok Pesantren Irshad Al Ibad Genukwatu Ngoro Jombang. The method is designed to simplify and systematically teach Arabic grammar rules to enhance the understanding and reading skills of traditional Arabic texts, crucial for their religious education. This research employs a qualitative approach to collect and analyze data through in-depth interviews with students and teachers, direct observations during the learning process, and analysis of relevant educational documents. The results indicate a significant improvement in students' abilities to read and interpret classical texts after implementing the method. The study found that students developed a better understanding of Arabic grammar rules and became more proficient in applying them. Additionally, the method increased students' motivation and active participation in the learning process. The significance of this study lies in its potential to provide a valuable contribution to the field of Arabic grammar education in religious schools. By demonstrating the effectiveness of the Nahwu Abstrak method, the research offers insights into innovative approaches that can address gaps in traditional grammar teaching methods and improve the overall quality of religious education.